Interobserver Reliability of Tongue Diagnosis Using Traditional Korean Medicine for Stroke Patients. (28th February 2012) - Ko, Mi Mi; Lee, Ju Ah; Kang, Byoung-Kab; Park, Tae-Yong; Lee, Jungsup; Lee, Myeong Soo
Abstract : Observation of the tongue, also known as tongue diagnosis, is an important procedure in diagnosis by inspection in Traditional Korean medicine (TKM). We investigated the reliability of TKM tongue diagnosis in stroke patients by evaluating interobserver reliability regarding tongue indicators as part of the project named the Fundamental Study for the Standardization and Objectification of Pattern Identification in TKM for Stroke (SOPI-Stroke). A total of 658 patients with stroke admitted to 9 oriental medical university hospitals participated. Each patient was independently seen by two experts from the same department for an examination of the status of the tongue. Interobserver agreement about subjects regarding pattern identification with the same opinion between the raters (n = 451 ) was generally high, ranging from "moderate" to "excellent". Interobserver agreement was nearly perfect for certain signs of special tongue appearance (mirror, spotted, and bluish purple), poor for one of the tongue colors (pale) and moderate for others. Clinicians displayed measurable agreement regarding tongue indicators via both observation and pattern identification consistency. However, interobserver reliability regarding tongue color and fur quality was relatively low. Therefore, it is necessary to improve objectivity and reproducibility of tongue diagnosis through the development of detail-oriented criteria and enhanced training of clinicians.